A qualitative analysis of unintended effects of a digital conditional cash transfer intervention to encourage healthcare utilization in Southern Madagascar - Mara Anna Franke; Anne Neumann; Kim Nordmann; Daniela Suleymanova; Onja Gabrielle Ravololohanitra; Samuel Knauss; Julius Valentin Emmrich (BMC Health Services Research)
Abstract Introduction Cash transfer interventions, including those using mobile money, are becoming increasingly widespread, particularly in Sub-Saharan Africa. As such interventions can have significant positive and negative unintended consequences, further analyses are needed to identify these consequences. Methods We investigated the unintended consequences of a digital conditional cash transfer intervention implemented at fifteen health facilities in Southern Madagascar. The intervention offered partial cost coverage for patients seeking care for potentially life-threatening conditions, accidents and injuries, maternal or pediatric care between February 2021 and June 2022. We conducted a qualitative analysis of in-depth interviews with policymakers, healthcare providers, (non-) beneficiaries of the intervention, and staff that implemented the intervention using reflexive thematic analysis. Results We identified three key positive and three key negative unintended consequences of the intervention. The key positive unintended consequences were: i) improved quality of care, ii) improved interpersonal relationships, including between patients and providers and between healthcare providers, and iii) digital skills development of healthcare providers and increased trust in mobile money. The three key negative consequences we identified were i) facility overcrowding, ii) an increase in costs of care, and iii) cases of hospital imprisonment. Conclusions Designers and implementers of future (digital) cash transfer interventions should carefully consider and proactively seek to leverage the positive and mitigate the negative unintended consequences of cash transfer interventions for healthcare such as those highlighted in our work.